Statistical optimization of medium components and physicochemical parameters to simultaneously enhance bacterial growth and esterase production by Bacillus thuringiensis - Mazzucotelli, Cintia Anabela (2015)
Bacillus thuringiensis is a genus extensively studied because of its high potential for biotechnological application, principally in biocontrol techniques. However, the optimization of esterase production by this strain has been scarcely studied. The aim of this work was to select and optimize the physicochemical and nutritional parameters that significantly influence the growth and esterase production of B. thuringiensis. To this purpose, 6 nutritional factors and 2 physicochemical parameters were evaluated using a Plackett-Burman design. Significant variables were optimized using a Box-Behnken design and through the desirability function to select the levels of the variables that simultaneously maximize microbial growth and esterase production. The optimum conditions resulting from simultaneous optimization of the responses under study were found to be 1 g/L glucose, 15 g/L peptone, and 3.25 g/L NaCl. Under these optimal conditions, it was possible to achieve a 2.5 log CFU/mL increase in bacterial growth and a 113-fold increase in esterase productivity, compared with minimal medium without agitation.